The roles of the capable others in developing learner autonomy ability in writing: reflection in a web-based learning community - Abdullah, R.; Ahmad, N.; Abdullah, A.; Mohd. Nor, N. (International Journal of Engineering and Technology, 2018)
This study explores the roles played by the capable others in developing a second-language writerâ€™s autonomy ability in writing; reflection in particular. The study focuses on how the capable others i.e. peers, through web-based peer feedback assisted the writer to reflect wisely.Â Â Nine peers, responded to the writerâ€™s essays on the writerâ€™s blog entries. Data was collected from the written web-based peer feedback, interviews and essays. The data was analyzed using thematic analysis. The findings suggest that the writer benefitted from the roles played by the peers in four categories: establishment of e-learning community, motivation, monitoring, and scaffolding. Establishment of e-learning community and motivation were found to have indirect impacts whilst monitoring and scaffolding have direct impacts on developing the writerâ€™s reflection ability.Â Â